Narcolepsy, Infections, and Autoimmunity (2015)
Narcolepsy is a neurological disorder characterized by excessive daytime sleepiness. It is caused by the loss of orexin-producing neurons in the lateral hypothalamus. There is evidence suggesting an autoimmune-mediated process may be the cause of the specific loss of orexin-producing neurons. In particular, there is a strong association with HLA DQB1?06:02 and other polymorphisms in immune-related genes. Moreover, onset of narcolepsy has been related with H1N1 and streptococcal infections, as well as with a dramatic increase of cases after the implementation of the ASO3-adjuvant H1N1 vaccine. This chapter shows how the immune system may be involved in the disease since the precise mechanism remains unknown. However, the possible causes and immunological pathways that can lead to an autoimmune destruction of orexin-producing neurons, such as molecular mimicry, bystander activation, and the combination of genetic and environmental factors are discussed. © 2015 Elsevier B.V. All rights reserved.